Anders Zorn: 130 Master Etchings (Master Drawings) - Zorn, Anders, 1860-1920; Kiroff, Blagoy; CreateSpace Independent Publishing Platform (United Kingdom : [CreateSpace Independent Publishing Platform], 2017)
Anders Zorn was one of Sweden s foremost artists who obtained international success as a painter, sculptor and printmaker in etching. His incisive ability to depict the individual character of his model is famous. The model's surroundings were important; Zorn believed that a portrait should be painted in an environment that was natural for the model. An artificial studio environment was not to his taste. The international esteem Zorn received was not based solely on his paintings but he was an exquisite etcher as well. He had worked with this technique since 1882. He had developed his abilities and was now highly accomplished. Zorn produced 289 etchings, a number of which are very well known, among them the portrait of Ernest Renan (1892), August Rodin (1906) and August Strindberg (1910). Zorn admired and collected the etched works of Rembrandt and considered him to be his artistic forefather in this particular medium.
Keywords: Zorn, Anders, -- 1860-1920 -- Catalogs